Estill Voice Training and voice quality control in contemporary commercial singing: an exploratory study. (2nd October 2017) - Fantini, Marco; Fussi, Franco; Crosetti, Erika; Succo, Giovanni
Abstract: Estill Voice Training (EVT) is a widely known programme for developing vocal skills based on partitioning the process of vocal production in order to reach control of specific structures in the vocal mechanism. The present retrospective small-scale exploratory study aims at reporting preliminary data about the efficacy of EVT – in terms of voice quality control on a specific vocal exercise – in contemporary commercial singers with a Certificate of Figure Proficiency (CFP). Thirty-five contemporary commercial singers (professional or semi-professional pop and rock singers) with no vocal complaints were recruited. The experimental group was composed of twenty singers who studied EVT and had a CFP. The control group was composed of fifteen singers who studied in Italian contemporary popular music institutions but were not familiar with EVT. Voice quality control was assessed through acoustic and perceptual analysis on a specific vocal exercise requiring sound pitch, perturbation and spectral energy distribution control. The acoustic analysis showed some significant differences between the two groups of singers both in sound perturbation control and spectral energy distribution control, suggesting a higher voice quality control ability for the experimental group. The perceptual evaluation confirmed a higher ability for the experimental group to produce recognizable voice qualities in this specific task. The reported preliminary results seem to suggest EVT as an effective educational system for developing voice quality control ability in contemporary commercial singers.